CPM for Project Scheduling: Case Study in Karbala Metal Silo - Fakhruddin Saleh, Hayman; Saad Khalaf, WaKas; Mohammed Abualrejal , Hussein (Journal of Economics and Administrative Sciences, 2024)
The understanding of techniques called project scheduling methods, and the delay in the completion of the Karbala metal silo in the holy province of Karbala is the non-use of modern techniques in implementation, so the research sought to provide the use of project scheduling using one of the advanced scientific methods that have proven the extent of its ability to schedule any project and its projects are the trade-off between time and the cost of completing the project . The objective of this research is to find the time and cost of completing the silo project in normal and crash conditions using CPM, which will facilitate the marketing of local wheat from the farmer and export it to mills. MS-Project was used to find the critical path. The cost distribution method was also used according to early start (ES) and latest start (LS) methods for calculating the process of distributing the costs of project activities and determining the area of financial savings when implementing project activities. The results obtained showed the importance of CPM and its efficiency in project scheduling, as the project was completed in normal conditions in 396 days and a total cost of 5,012,811,028 ID. However, when activities were crashed, the project completion time was 307 days and a total cost of 5,043,894,328 ID. The results also proved that using the method of allocating costs according to the LS method helped the decision maker to determine the area of financial abundance and the limits of financial maneuvering that he can perform during the completion of the project activities